(untitled) (Research, Society and Development, 2021)
The innovative process becomes essential for organizations, as it adds value to products, processes and services, keeping the company in the market and generating competitive advantage, aware that companies seek to manage more and more new ideas. In this context, the generation and management of ideas becomes a necessary factor for the promotion of organizational management amid high competitiveness and increasingly fierce markets. This article aims to present the development of a model for the expansion of organizational competitive advantage that makes it possible to assist and add value to decisions in organizations. Bibliographic references methodology was used in view of the new proposal. Existing managerial elements were also used to base this new proposal. The search for insertion of new management tools becomes extremely relevant in organizational growth regardless of the organization to be studied or applied, where the search for the growth of the people involved must also be taken into account, stimulating socio-environmental issues.